Strengthening Geospatial Literacy Through High School–University Collaboration: A Multi-Site Tiered Desktop–Cloud GIS Model - Roni Alim Ba'diya Kusufa; Achmad Maulana Malik Jamil; Abdul Fakih; Jovanka Diva Indriana (JAMBURA GEO EDUCATION JOURNAL, 2026)
Geospatial literacy is increasingly important for students’ ability to interpret spatial information and solve data-based problems. However, many Indonesian schools still face constraints in teacher readiness, technological infrastructure, and contextualized learning materials. This study investigates how structured high school–university collaboration can strengthen geospatial literacy through a collaboration-management model and a tiered desktop–cloud GIS learning pathway. It used a qualitative multi-site instrumental case study with embedded quantitative descriptive indicators, including a program-suitability survey and pre/post rubric-based competency scores. Data were collected through interviews, observations, focus group discussions, questionnaires, and document analysis across three collaboration sites in Jakarta–Depok, Yogyakarta, and Bandung. Five interrelated components shaped implementation: collaborative governance, a tiered competency-based curriculum, open, shared geospatial infrastructure (QGIS, Google Earth Engine, and OpenStreetMap), sustained teacher professional development, and authentic project-based learning. Program suitability was high overall (84.6% Agree/Strongly Agree), students produced 45 GIS-based projects, and 89% of participants completed the required artifacts for their assigned tier. Mean rubric scores improved from pre to post in spatial analysis (45–82), GIS software proficiency (38–79), geospatial problem-solving (42–78), and data interpretation (51–85). Improvements are reported as absolute, normalized, and relative gains, with caution that relative gain may overstate change when baseline scores are low. The findings provide a reusable collaboration and implementation model for expanding desktop–cloud GIS learning in secondary education; the quantitative indicators triangulate the qualitative evidence and should not be interpreted as causal effects.